Debate-Based Learning and Its Impact on Students’ Critical Thinking Skills - Narmaditya, Bagus Shandy; Omar, Intan Marfarrina Binti (Unversitas Negeri Malang, 2019)
This study aims at understanding the implementation of debate-based learning models on critical thinking skill of economic students in senior high school. This research was conducted in a senior high school in Malang particularly in SMA Laboratory UM. The study applied a classroom action research by comparing students’ critical thinking skills during research period. The level of critical thinking skill adopted Structure Observed Learning Outcome (SOLO) Taxonomy which consisting of Prestructural, Unistructural, Multistuctural, Relational, and Extended Abstract Thinking Skills. The findings showed that a remarkable change of students’ critical thinking skills during cycles. The average of post-test score between cycles increased by 11.9 percent. In addition, the level of students critical thinking skill was dominated by Prestructural, Unistructural, Multistructural then it move noticeably to the greater level which is Multistructural, Relational and Extended Abstract. From these results,it can be concluded that the implementation of debate-based learning can stimulate students’ learning activities and critical thinking skills.Keywords: Debate-Based Learning, Critical Thinking, Students’ Activities